Towards a resilient labour movement: reforming trade union practices in Malaysia - Mohd Yusof, Noorlailahusna; Rusli, Noorayuni; Hammad Ahmad Khan, Hafizah (Universiti Teknologi MARA Selangor, 2025)
The labour movement in Malaysia, mirroring global trends, faces major challenges such as declining union membership, restrictive legislative frameworks, and limited adaptation to technological and demographic changes. This study aims to propose reforms that enhance the resilience and relevance of Malaysian trade unions in a rapidly evolving labour landscape. Using a conceptual analysis approach, supported by case studies and international comparative practices, the study examines structural, legislative, and operational barriers affecting unions. Key findings reveal fragmentation among unions, outdated legislation, and low engagement with younger workers and those in the gig economy. Recommendations include consolidating unions, integrating good faith bargaining into the Trade Unions Act 1959, and utilising digital tools for member engagement. Drawing from successful global practices such as union-employer partnerships in Scandinavia the study underscores the importance of leadership capacity-building and alignment with international labour standards. These reforms are essential for revitalising Malaysia’s trade unions, strengthening equitable labour relations, and contributing to socioeconomic stability. Moreover, the study highlights the broader societal value of a resilient labour movement in achieving Malaysia’s vision for inclusive and sustainable national development.